Block chain based IAS protocol to enhance security and privacy in cloud computing - S. Navin Prasad; C. Rekha (Measurement: Sensors, 2023)
Cloud computing has become increasingly popular for data storage and processing, but security and privacy remain major concerns due to the potential for malicious attacks on wireless and mobile communication networks. In order to address these issues, researchers have proposed an IAS protocol that incorporates identity, access control, and secure authentication. To ensure the authenticity and security of data transmission in cloud computing, the proposed IAS protocol is implemented on top of blockchain technology. This allows for decentralized key management for recovery and revocation, as well as identity verification. To evaluate the effectiveness of this approach, the proposed model using Block Chain based Identity Management, Access Control and Secure Sharing (BC-IAS) is simulated on the cloud environment. The simulation assesses primary performance key metrics, including Data Access Rate, Message Delivery Ratio, End to End Delay and Energy consumption. Overall, the proposed BC-IAS protocol on top of blockchain technology shows promise for enhancing security and privacy in cloud computing. The proposed BC-IAS protocol on top of blockchain technology presents a promising solution for enhancing the security and privacy of cloud computing. The decentralized nature of blockchain technology ensures that data is stored in a tamper-proof and transparent manner, while the use of smart contracts allows for automated enforcement of access control policies. Moreover, the incorporation of identity verification and secure authentication ensures that only authorized users can access sensitive data, reducing the risk of data breaches and cyber-attacks.